h - Cruickshank, Ruth, 1967- (Oxford : Oxford University Press, 2009)
In this closely analytical study, Cruickshank reads the work of four influential writers of prose fiction - Angot, Echenoz, Houellebecq, and Redonnet - in the context of the turn of the millennium in France, which coincided with a number of tangible crises and apocalyptic discourses, and with the growth of the mass media and global market.
Includes bibliographical references.
Description based on print version record.
Includes index.
Keywords: French fiction -- 20th century -- History and criticism; French fiction -- 21st century -- History and criticism; Echenoz, Jean -- Criticism and interpretation; Houellebecq, Michel -- Criticism and interpretation; Angot, Christine -- Criticism and interpretation; Redonnet, Marie -- Criticism and interpretation